2014
DOI: 10.7863/ultra.33.11.1999
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Findings in Patients With Crimean‐Congo Hemorrhagic Fever

Abstract: Hepatosplenomegaly, paraceliac lymphadenopathy, and gallbladder wall thickening as well as intraperitoneal and pleural effusion were the primary findings in CCHF, and they became prominent on the third day of the disease in some patients. The relationship between sonographic findings and disease severity will be investigated in an upcoming study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The patients were usually severe cases and had been admitted with hemorrhagic symptoms. Hepatomegaly (40%), splenomegaly (28%), paraceliac lymphadenopathy (48%), gallbladder wall thickening (36%), increased echogenicity in the renal parenchyma (40%), and fluid/effusion in the perihepatic, perisplenic, pleural, and hepatorenal recesses (52%) were the primary findings [Tufan et al, ]. In another study which included 210 patients with CCHF, sonographic findings revealed that the presence of ascites is a very rare complication observed in only 1.4% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were usually severe cases and had been admitted with hemorrhagic symptoms. Hepatomegaly (40%), splenomegaly (28%), paraceliac lymphadenopathy (48%), gallbladder wall thickening (36%), increased echogenicity in the renal parenchyma (40%), and fluid/effusion in the perihepatic, perisplenic, pleural, and hepatorenal recesses (52%) were the primary findings [Tufan et al, ]. In another study which included 210 patients with CCHF, sonographic findings revealed that the presence of ascites is a very rare complication observed in only 1.4% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 Radiologic findings include hepatomegaly, splenomegaly, paraceliac lymphadenopathy, and effusion in the perihepatic, perisplenic, pleural, and hepatorenal recesses of the subhepatic space as well as between the intestinal loops. 4,5 Diagnosis of CCHF is based on detection of viral RNA by real time reverse transcriptase-polymerase chain reaction (RT-PCR) and/or the presence of specific IgM antibodies (viral nucleocapsid and glycoprotein precursor antibodies: N-IgM and GPC-IgM). 6 Although many studies have tried to clarify the pathogenesis of CCHF, advances have been limited due to the virulence of the disease, which complicates animal studies.…”
Section: Introductionmentioning
confidence: 99%
“…88 Similarly, in a multivariate analysis in CCHF, gallbladder wall thickening, and intra-abdominal fluid collections were found to be significantly associated with disease severity. 89,90 Validation of a standardized POCUS protocol to diagnose and predict severity of VHF in epidemic situations and to adapt monitoring and supportive treatment accordingly appears worthwhile.…”
Section: Other Infectious Diseases With Potential For Pocus Applicationmentioning
confidence: 99%